Carbamylated form of human erythropoietin normalizes cardiorespiratory disorders triggered by intermittent hypoxia mimicking sleep apnea syndrome. Issue 6 (June 2021) - Andrade, David C.; Toledo, Camilo; Diaz, Hugo S.; Pereyra, Katherin V.; Schwarz, Karla G.; Díaz-Jara, Esteban; Melipillan, Claudia; Rios-Gallardo, Angélica P.; Uribe-Ojeda, Atenea; Alcayaga, Julio; Quintanilla, Rodrigo A.; Iturriaga, Rodrigo; et al.
Abstract : Background and objective: Chronic intermittent hypoxia (CIH), one of the main features of obstructive sleep apnea (OSA), enhances carotid body-mediated chemoreflex and induces hypertension and breathing disorders. The carbamylated form of erythropoietin (cEpo) may have beneficial effects as it retains its antioxidant/anti-inflammatory and neuroprotective profile without increasing red blood cells number. However, no studies have evaluated the potential therapeutic effect of cEpo on CIH-related cardiorespiratory disorders. We aimed to determine whether cEpo normalized the CIH-enhanced carotid body ventilatory chemoreflex, the hypertension and ventilatory disorders in rats. Methods: Male Sprague–Dawley rats (250 g) were exposed to CIH (5% O2, 12/h, 8 h/day) for 28 days. cEPO (20 μg/kg, i.p) was administrated from day 21 every other day for one more week. Cardiovascular and respiratory function were assessed in freely moving animals. Results: Twenty-one days of CIH increased carotid body-mediated chemoreflex responses as evidenced by a significant increase in the hypoxic ventilatory response (Fi O2 10%) and triggered irregular eupneic breathing, active expiration, and produced hypertension. cEpo treatment significantly reduced the carotid body–chemoreflex responses, normalizes breathing patterns and the hypertension in CIH. In addition, cEpo treatment effectively normalized carotid body chemosensory responses evoked by acute hypoxic stimulation in CIH rats. Conclusion: Present results strongly support beneficial cardiorespiratory therapeutic effects of cEpo during CIH exposure. Abstract : Supplemental Digital Content is available in the text